India's Maritime Heritage - K Sreedharan; SRIDHARAN (K) (New Delhi CBS Publishers And Distributors, 2003)
This unique and richly illustrated book depicts 3500 years of Indiamaritime heritage. Starting from ancient times India maritime progress has been traced to the present day. The wide range of pictures is enhanced by the succinct text and captions that together cover various facets of Indias advancement in shipbuilding shipping maritime commerce a cultural interaction across the seas.
Keywords: Indian Navy